Teoría de juegos aplicada a la toma de decisiones en contextos empresariales competitivos en el mercado de bicicletas y motocicletas; Game theory applied to decision making in competitive business contexts in the bicycle and motorcycle market - Carlos Ernesto Flores Tapia; Santiago Mauricio Loza Sánchez; Nadia Micaela Zamora Flores; Lissette Flores Cevallos (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2023)
– This article applies game theory in the company under study, in order to optimize the competitive strategy with respect to its main competitor in the bicycle and motorcycle market. Once the problem is defined, the zero-sum matrix between the competitors is established, then the model is processed using the corresponding mathematical model and the strategy that allows the best positioning in the market is selected. In addition, it is proven that, eventually, if the competitive strategic decisions are modified, it affects, in turn, the decision-making of rival companies, consequently in the strategic decision of the company taken as a case study. The objective of the study is to explain how game theory helps decision making through the application of tools and factors that determine the degree of importance in the organization. This research is quantitative, allowing the use of systematic processes to study the problem. This study has an explanatory scope, since it tries to establish the causes, the environment and the consequences, in this case, related to aspects of competitiveness linked to the company under study, applying game theory. The result of the investigation indicates that the implementation of game theory in the Motocentro company will help to achieve more sales of articles for bicycles and motorcycles, depending on the value assigned to the strategies established by the company.
Keywords: C02; C72; M21; L21; L25; L62; 330; Operations Research; Game Theory; Strategy; Business Administration; Competitive Markets